A review of g-C3N4 based catalysts for direct methanol fuel cells. (15th January 2022) - Yuda, Afdhal; Kumar, Anand
Abstract: Direct methanol fuel cells (DMFC) possess numerous advantages for powering portable mobile devices. However, there are still major challenges in their development and commercialization that originates from the anode catalyst responsible for methanol oxidation reaction. This has motivated researchers to find a cost effective and durable catalyst material for methanol oxidation. Recently, carbon-based 2-D graphitic carbon nitride (g-C3 N4 ) has been found to have good potentials to catalyse alcohol oxidation reactions in fuel cells. This review provides a summarized information of previously developed g-C3 N4 -containing-electrocatalysts based on the active sites present (e.g., non-metals, noble metals, and non-noble metals) for methanol electro-oxidation to compare their electrocatalytic performance. It also consists of brief examination of their structure, description of different synthesis methods and post-synthesis treatments, and evaluation of their properties that contributes to their resulting performance. The review then concludes with the details of challenges and possible solutions that enable DMFC to be a reliable source of energy in the future. Highlights: g-C3 N4 based MOR catalyst with noble metals and non-noble metals are presented. Synthesis methods and photo/electro-catalytic properties of g-C3 N4 are described. Structural modifications and doping of g-C3 N4 can lead to better performance. CO poisoning is a major challenge, and catalysts tolerant to CO are discussed. Challenges faced in MOR and critical points for future research are proposed.